Junior High School Students' Perceptions of Learning Tenses Through the Tiktok Application - Muhammad Faruq Alauddin (Universitas PGRI Yogyakarta, 2023)
ABSTRACTThis study was based on the opinions of students who used the widely popular TikTok program to learn tenses. For this reason, we looked into how the Tiktok application influenced students' enthusiasm in studying tenses. (1) To discover more about how students feel about studying tenses in general and specifically using the tiktok application (2) evaluating the outcomes of learning tenses just in the classroom versus learning tenses using the Tik Tok app. This study uses seven respondents from junior high schools who are just learning about tenses and employs qualitative research techniques to collect data from surveys on a google form. According to the study's findings, four students thought utilizing Tiktok as a learning tool for learning tenses was beneficial. It implies that the Tiktok is a tool for him to increase his understanding of tenses. As a result, using TikTok as a learning tool to practice tenses makes the process of learning a new language more enjoyable, dynamic, and interesting.. So from this research, we can conclude that learning media in studying tenses is very necessary so that students do not only get information from one source. keywords: tenses, junior high school students, learning media, the Tik Tok application.